2021
DOI: 10.1016/j.radonc.2021.01.029
|View full text |Cite
|
Sign up to set email alerts
|

The role of combined ion-beam radiotherapy (CIBRT) with protons and carbon ions in a multimodal treatment strategy of inoperable osteosarcoma

Abstract: Background: To investigate the role of combined ion-beam radiotherapy (CIBRT) with protons and carbon ions in a multimodal treatment strategy of inoperable osteosarcoma; final analysis of a one-armed, single center phase I/II trial. Methods: Between August 2011 until September 2018, 20 patients with primary (N = 18), metastatic (N = 3), or recurrent (N = 2) inoperable pelvic (70%) or craniofacial (30%) osteosarcoma were treated with protons up to 54 Gy (RBE) and a carbon ion boost of 18 Gy (RBE) and followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
11
1
2
Order By: Relevance
“…Most adverse events were grade 2 or lower, and the reasonably high OS suggests particle beam therapy (carbon and proton) for BSS-HN might be a possibility in the future. However, despite the proton and C-ion boost intervention, the OS in the previous study (15) was slightly lower than that of our study. Lower OS might be related to lower LC and PFS.…”
Section: Discussioncontrasting
confidence: 94%
“…Most adverse events were grade 2 or lower, and the reasonably high OS suggests particle beam therapy (carbon and proton) for BSS-HN might be a possibility in the future. However, despite the proton and C-ion boost intervention, the OS in the previous study (15) was slightly lower than that of our study. Lower OS might be related to lower LC and PFS.…”
Section: Discussioncontrasting
confidence: 94%
“…Currently, the event-free survival of OS patients is about 60–70% after neoadjuvant CT comprising cisplatin, doxorubicin followed by high-dose methotrexate, and surgical removal of the tumor often followed by adjuvant CT. EBRT plays no or only a minor role due to the high radioresistance of OS and is only applied on rare occasions when surgical margins are limited by tumor localization with an additional positive impact on prognosis, but high doses up to 80 Gy may be required to achieve some additional benefit [ 390 ]. Here, recent studies using highly localized combined ion-beam EBRT for inoperable OS showed promising results and may represent a treatment option with a favorable toxicity profile [ 364 ].…”
Section: Childhood Cancer and Second Primary Malignanciesmentioning
confidence: 99%
“… 10 Modern radiotherapy techniques such as proton therapy may save the occasional patient when complete surgery is not an option. 11 , 12 However, complete surgery must remain the first choice in all cases.…”
Section: Local Therapy: From the Oncologist’s Viewmentioning
confidence: 99%